Race and Social Class Analysis in the Series ‘QUEEN CHARLOTTE: A Bridgerton Story’ - Salsabila, Azzehra; Hasanah, Atiq Aqiqotul; Mariana, Ana; Otoluwa, Moon Hidayati; Ntamwana, Simon; Mukhsin, Hasna Nurain (Journal of English Language Teaching, Linguistics, and Literature Studies, 2025)
Queen Charlotte: a Bridgerton Story a series created by Shondaland and released by Netflix, is a drama series that took place during the Regency era in England. The series is based on historical stories portrayed as a fiction and offers a reinterpretation of the British aristocracy through an inclusive modern lens. This study aims to examine how issues of race and social class are represented in the dialogue narrative and how does this influence the dynamics of the characters in the drama series ‘Queen Charlotte: a Bridgerton Story’. By using qualitative method and using theoretical concepts of double consciousness and the veil by W.E.B Du Bois, this study aims to giving an understanding of how race and social class are connected and shape the experiences of minority group characters who are not understood by majority group characters in the series. The result of this study shows that minority group characters who experience identity conflict inside themselves are showing changes, particularly in the way they navigate their social positions and shape their identities in the middle of a society that is still hierarchical.Keywords: Race, Social Class, Double Consciousness, Veil, Bridgerton